A homogeniser inspired by the crustacean's eye with uniform irradiance distribution and high optical efficiency characteristics for concentrated photovoltaics system. (June 2021) - Vu, Duc Tu; Vu, Hoang; Vu, Ngoc Hai
Highlights: A homogeniser inspired by the crustacean's eye using for the CPV system. Such homogeniser can evolve a uniform version of light distribution. The best structure displays a uniformity 85% and an optical efficiency 90%. Toward relaxing a secondary mirror in the existing CPV system using a parabolic mirror. Abstract: We devise an implicitly new design for boosting the light uniformity in the concentrated photovoltaics (CPV) system, whereby addressing the overheating issue of the PV cell and enhancing the electrical cell efficiency. Rather than using a well-known system of the Cassegrain concentrator design, consisting of double mirrors + a homogeniser, in this study, we mimic a structure of crustacean's eyes for a design of homogeniser, consisting of an array of a mirror channel. Such proposed design allows making use of only a primary parabolic mirror + a homogeniser to concentrate and redistribute the sunlight, representing a large departure from virtually all of the previous studies. Specifically, such homogeniser can furcate the light beam into the small channels/trenches, redirect the light ray at the reflective plate and probably mix them to evolve a uniform version of light distribution. In general, the homogeniser can affect the uniformity and optical efficiency, which are good probes to assess the light performance, in a number of ways. We found that light performance depends sizably on the structural parameters such as the size and the number of channels of the homogeniser. The best structure displays a calculated uniformity of 85% of the flux distribution on solar cell and a calculated optical efficiency of 90% of the entire CPV system. We also assess the light performance against some scenarios of error in installation and operation processes such as tolerance and misalignment and compare well with the current design. The compelling of this proposed design is highly efficient light performance, compactness and inexpensive, which likely address virtually existing bottlenecks in the CPV system.